EDUKASI PEMBENTUKAN BISNIS UNTUK MENCIPTAKAN KEMANDIRIAN FINANSIAL BAGI MAHASISWA - Ketut Widya Kayohana ketut; L. Jatmiko Jati, miko; Muhamad Wisnu Alfiansyah wisnu; Susilo Talidobel susilo (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
The food and beverage department is the part whose job is to take care of the food and beverage service needs of customers In NTB itself, especially the city of Mataram, the interest in shopping for people is quite high because it can be seen with the existence of concert events and so on, opening up opportunities for MSMEs in introducing their products. FGD (Focus Group Discussion) method to students to provide knowledge, increase understanding and awareness of partners regarding business and technology utilization to increase business levels. Technically, there are 2 meeting sessions with partners. The results of the service obtained where the service was carried out with partners made a cake named "milkbath cake" and several other types of food such as sweets/dessert (dessert). The team targets our products for all economic circles using SWOT analysis. The sales result for 3 months starting from November to January was Rp1,375,000. Where the sales of each product is 25 pcs, the bundling package of both products (noohun and pochil) sold as many as 25 packages. cost control using two ways (fixed cost, variable cost)